Hemocyanin of the caenogastropod Pomacea canaliculata exhibits evolutionary differences among gastropod clades - Chiumiento, Ignacio Rafael (2020)
Structural knowledge of gastropod hemocyanins is scarce. To better understand their evolution and diversity we studied the hemocyanin of a caenogastropod, Pomacea canaliculata (PcH). Through a proteomic and genomic approach, we identified 4 PcH subunit isoforms, in contrast with other gastropods that usually have 2 or 3. Each isoform has the typical Keyhole limpet-type hemocyanin architecture, comprising a string of eight globular functional units (FUs). Correspondingly, genes are organized in eight FUs coding regions. All FUs in the 4 genes are encoded by more than one exon, a feature not found in non- caenogastropods. Transmission electron microscopy images of PcH showed a cylindrical structure organized in di, tri and tetra-decamers with an internal collar structure, being the di and tridecameric cylinders the most abundant ones. PcH is N-glycosylated with high mannose and hybrid-type structures, and complex-type N-linked glycans, with absence of sialic acid. Terminal β-N-GlcNAc residues and nonreducing terminal α-GalNAc are also present. The molecule lacks O-linked glycosylation but presents the T-antigen (Gal-β1,3-GalNAc). Using an anti-PcH polyclonal antibody, no cross-immunoreactivity was observed against other gastropod hemocyanins, highlighting the presence of clade-specific structural differences among gastropod hemocyanins. This is, to the best of our knowledge, the first gene structure study of a Caenogastropoda hemocyanin.